G551(P) Complications of hyperleukocytosis in acute leukaemia: wcc risk threshold analysis. (May 2019) - Carver, A; Katz, T; Round, J; Prince, N
Abstract : Aims: Acute leukaemia presenting with hyperleukocytosis (white cell count (WCC) >50×10 9 /L) is associated with organ dysfunction due to hyperviscosity. However, there is little evidence to guide which children are at highest risk and who might benefit from aggressive leukoreduction, including leukapheresis. We explored whether it is possible to risk stratify children based on initial WCC and evaluated the role of leukapheresis in preventing complications of hyperleukocytosis. Methods: A retrospective analysis of all children with ALL or AML who were admitted to our tertiary paediatric oncology and critical care centre with an initial WCC >50×10 9 /L, 2007–2017. Results: 37 patients were identified (ALL: 28; AML: 9). Median age 6 years, 54% were male. All patients were treated with immediate hyperhydration and chemotherapy within 48 hours. 5 patients were treated with leukapheresis. 11 children (30%) developed complications (21% of ALL; 55% of AML): 27% respiratory, 14% neurological and 8% renal. Children who presented with hyperleukocytic complications tended to have a higher initial WCC than those without complications at presentation (Median: 332 vs. 175 × 10 9 /L). The initial WCC of children who developed complications later in their admission did not differ from the WCC of those without complications (Median: 161 vs. 175 × 10 9 /L), suggesting that later complications cannot be related to WCC at presentation. Severe events (stroke or early mortality) occurred in 4 children (11%). All 4 had complications at presentation and 3 were treated with leukapheresis. Conclusions: Several findings may be useful for risk stratification: Complications are more likely in AML than in ALL Complications did not occur with WCC <100 x10 9 /L Severe events occurred only in children with complications at presentation – those who present without complications appear to be low risk for the most dangerous events regardless of their initial WCC. 4 children with complications on admission were treated with leukapheresis yet all 4 developed further complications including 3 severe events. Therefore, leukapheresis did not help to avoid further complications. Early chemotherapy thus remains the most important aspect of clinical management and further research into the prevention of severe events is required.